Born of Lakes and Plains : Mixed-Descent Peoples and the Making of the American West - Hyde, Anne Farrar, 1960- (New York, NY : W. W. Norton & Company, 2022)
"A revealing history of the West that pivots on Native peoples and the mixed families they made with European settlers. There is mixed blood at the heart of America. And at the heart of Native life for centuries there were complex households using marriage to link communities and protect people within circles of kin. These family circles took in European newcomers who followed the fur trade into Indian Country from the Great Lakes to the Columbia River. Vividly combining the panoramic and the particular, Anne F. Hyde's pathbreaking history follows five mixed-descent families whose lives were inscribed by history: corporate battles over control of the fur trade, the extension of American power into the West, the ravages of imported disease, the violence triggered by Indian removal, the incessant battles for land with encroaching American settlement, and the mix of opportunity and disaster in post-Civil War reservations and allotment. Occupying a dangerous intermediate ground in a continent of conflict, mixed-descent families were pivotal in the events that made the West"--.
Ozhaguscodaywaquay and John Johnston : mixing blood in the fur trade, 1670-1790 -- Wintering families and corporate war, 1770-1810 -- Fur trade migrants : Pacific McKays and Canadian Johnstons, 1800-1820 -- "This kind of business will make trouble" : remaking the fur trade, 1810-1830 -- From the Sault to the Oregon Country : mingling blood and land, 1818-1838 -- Forging peace on the southern plains, 1821-1840 -- Rivers of trouble in Indian Country, 1831-1843 -- "Marked for slaughter" : borderland violence in the 1840s -- Surviving war and peace in the 1850s -- Civil wars in the West, 1860-1865 -- Reconstructing race on western reservations, 1866-1885 -- "A mighty pulverizing engine" : allotment policy and blood quantum, 1880-1907 -- Epilogue: The twentieth century.
Includes bibliographical references and index.
Keywords: Multiracial people -- West (U S ) -- History -- 19th century; Indians of North America -- West (U S ) -- History -- 19th century; Fur traders -- West (U S ) -- History; White people -- Relations with Indians; West (U.S.) -- History -- 19th century